1999
DOI: 10.1139/f99-171
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of the lamprey genusLampetrainferred from mitochondrial cytochromeband ND3 gene sequences

Abstract: Mitochrondrial DNA analysis resolved many previously unanswered questions concerning the phylogeny of the lamprey genus Lampetra (comprising the subgenera Entosphenus, Lethenteron, and Lampetra). A total of 735 base pairs were sequenced from the cytochrome b and NADH dehydrogenase subunit 3 (ND3) genes in 11 lamprey species. With the exception of L . (E.) hubbsi from California, species of the Entosphenus subgenus formed a tight-knit clade that was very distinct from the other two subgenera. Lampetra hubbsi cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 26 publications
8
77
0
Order By: Relevance
“…In selecting pairs of cyclostome species for Ks estimation, we treated the lamprey genus Lampetra as having the same distance the genus Lethenteron has from Petromyzon. This is based on a previous phylogenetic study using the cytochrome b and NADH dehydrogenase subunit 3 (ND3) genes (Docker et al, 1999), which is consistent with the classification by Potter (1980), who formerly considered that the three subgenera, Entosphenus, Lethenteron, and Lampetra, compose the single genus Lampetra. Despite the small number of genes sampled, similar Ks values were consistently obtained for Petromyzon-Lampetra and PetromyzonLethenteron pairs (Table 2).…”
Section: Ks As a Tool To Standardize Evolutionary Distancessupporting
confidence: 81%
See 2 more Smart Citations
“…In selecting pairs of cyclostome species for Ks estimation, we treated the lamprey genus Lampetra as having the same distance the genus Lethenteron has from Petromyzon. This is based on a previous phylogenetic study using the cytochrome b and NADH dehydrogenase subunit 3 (ND3) genes (Docker et al, 1999), which is consistent with the classification by Potter (1980), who formerly considered that the three subgenera, Entosphenus, Lethenteron, and Lampetra, compose the single genus Lampetra. Despite the small number of genes sampled, similar Ks values were consistently obtained for Petromyzon-Lampetra and PetromyzonLethenteron pairs (Table 2).…”
Section: Ks As a Tool To Standardize Evolutionary Distancessupporting
confidence: 81%
“…The assembled sequences are available upon request. In analyses using the GCcontent of the third positions (GC3), we obtained similar results for all the graphs in this We treated the genus Lampetra as equally distant from Lethenteron in relation to Petromyzon based on the previous molecular phylogenetic study (Docker et al, 1999). Goldman and Yang (1994); PBL, Calculated with the method by Pamilo and Bianchi (1993) and Li (1993).…”
Section: Estimated Number Of Synonymous Substitutionsmentioning
confidence: 63%
See 1 more Smart Citation
“…Non-parasitic and parasitic species pairs (Potter 1980b) or satellite species (Vladykov and Kott 1980) co-occur in many river systems. Often, members of paired and satellite species are not even genetically distinguishable (Docker et al 1999). Due to unreliable species identification techniques, researchers have resorted to holding specimens until metamorphosis (Heard 1966;Beamish 1980), conducting post-hoc genetic or morphological identification (Filcek et al 2005;Meeuwig and Bayer 2005), or sampling only above impassable obstacles, where anadromous parasitic forms do not occur (Maitland 2003).…”
Section: Considerations For Sampling Designmentioning
confidence: 99%
“…The genus Lampetra is further divided into three sub-genera, Entosphenus, Lethenteron, and Lampetra, with Lampetra being the most derived of the subgenera. A recent study used two mitochondrial genes to examine the phylogeny of Lampetra, and found evidence for Entosphenus to be a separate taxon, but that the division between Lethenteron and Lampetra does not exist and that this combined group is derived from Entosphenus (Docker et al, 1999). Although it has not been established whether all the lamprey species can produce PZS during their larval stage, it is likely that PZS is common among larval lampreys, based on a recent study that revealed that larvae of Pacific and western brook lampreys can …”
Section: Elisa Analysismentioning
confidence: 99%